(untitled) - Joc Potter (Oxford, 2000)
Every year some species of animal disappear - we never see them again, Every year cities, factories and pollution eat up more land - land that animals need. Every hunters kill more elephants, rhinoceros and tigers. Animals everywhere are in danger - waht can the world do to save them?
Keywords: almanacs,curiosities and wonders